2021
DOI: 10.1002/arch.21781
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses and weighted gene coexpression network analysis reveal key pathways and genes involved in the rapid cold resistance of the Chinese white wax scale insect

Abstract: The Chinese white wax scale insect, Ericerus pela, is an important resource insect in China. The rapid response of E. pela to decreasing temperatures plays key roles in the population distribution. In this study, we analyzed the gene expression of E. pela treated with low temperature using transcriptome analyses and weighted gene coexpression network analysis (WGCNA). The results showed that the cold resistance of E. pela involved changes in the expression of many genes. The genes were mainly involved in alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(55 reference statements)
2
9
0
Order By: Relevance
“…Eight genes coding UDP-glucuronosyltransferases were determined to be the hub genes in insecticide resistance [ 80 ], which proved essential for the elimination and detoxification of drugs, xenobiotics, and chemical compounds [ 81 , 82 ]. In the study of Ericerus pela , the hub genes associated with cold resistance were identified by using WGCNA; some well-studied cold resistance-related genes, such as heat shock protein, and antifreeze protein, could be rediscovered by this method [ 83 ]. Through these studies, it was confirmed that many of the hub genes obtained by WGCNA analysis were indeed very important genes; the WGCNA method is reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Eight genes coding UDP-glucuronosyltransferases were determined to be the hub genes in insecticide resistance [ 80 ], which proved essential for the elimination and detoxification of drugs, xenobiotics, and chemical compounds [ 81 , 82 ]. In the study of Ericerus pela , the hub genes associated with cold resistance were identified by using WGCNA; some well-studied cold resistance-related genes, such as heat shock protein, and antifreeze protein, could be rediscovered by this method [ 83 ]. Through these studies, it was confirmed that many of the hub genes obtained by WGCNA analysis were indeed very important genes; the WGCNA method is reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Most Coccoidea species are agriculture and forestry pests, except for very few species with a high economic value, such as the Chinese white wax scale insect Ericerus pela (Chavannes, 1848) [ 17 ]. Previous work has related to E. pela ’s use in biological research, molecular research, and the popularization of relevant applications [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Regarding its breeding history, people initially started to collect white wax as early as approximately the 3rd century AD in China [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has related to E. pela ’s use in biological research, molecular research, and the popularization of relevant applications [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Regarding its breeding history, people initially started to collect white wax as early as approximately the 3rd century AD in China [ 26 ]. The wax produced by insects is an important commodity that has been widely applied in cosmetics, Chinese traditional medicine, the manufacturing industry (e.g., automotive and furniture manufacture), and the printing industry for more than one thousand years [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…, 2021; Zhang et al. , 2021a), insecticide resistance (Tian et al. , 2021), aggressive behavior (Rao et al.…”
Section: Introductionmentioning
confidence: 99%